2007
DOI: 10.1039/b709387j
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant formation of chiral and racemic crystals of a diaryl sulfide

Abstract: The conformationally chiral 10-nitro-phenanthren-9-yl phenyl sulfide is found to crystallise as one racemic phase and one chiral phase; the chiral phase undergoes total spontaneous resolution on crystallisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 21 publications
(21 reference statements)
1
11
0
Order By: Relevance
“…Several new crystallization attempts were performed under similar conditions and only the monoclinic phase was obtained. This behaviour seems to be not uncommon and has been previously (Dunitz & Bernstein, 1995) and recently reported (Lennartsson et al, 2007). In the alkylaminocarbonyl derivatives with ethyl as the alkyl group and with propyl instead of methyl substituents, crystals slightly different in shape appear in the same batch, but all were con®rmed to belong to the form described previously.…”
Section: Commentsupporting
confidence: 80%
“…Several new crystallization attempts were performed under similar conditions and only the monoclinic phase was obtained. This behaviour seems to be not uncommon and has been previously (Dunitz & Bernstein, 1995) and recently reported (Lennartsson et al, 2007). In the alkylaminocarbonyl derivatives with ethyl as the alkyl group and with propyl instead of methyl substituents, crystals slightly different in shape appear in the same batch, but all were con®rmed to belong to the form described previously.…”
Section: Commentsupporting
confidence: 80%
“…Over the years, we have studied the total spontaneous resolution of stereochemically labile chemical reagents (Lennartson et al, 2009;Vestergren et al, 2000Vestergren et al, , 2003Hå kansson et al, 1999) and potential substrates (Johansson & Hå kansson, 2005;Lennartson, Salo et al, 2005;Andersson et al, 1986, Lennartson et al, 2007. During a study of diphenylzinc complexes, it was found that diphenyldipyridinezinc(II), (I), crystallizes in the Sohnke space group P2 1 2 1 2.…”
Section: Commentmentioning
confidence: 99%
“…The compounds exhibit a phenomenon of concomitant crystallization of racemic and chiral phases [33,34]. The different phases can be easily distinguished according to the shape of crystals.…”
Section: Resultsmentioning
confidence: 99%